ANALISIS PELAKSANAAN SISTEM E-PUSKESMAS DENGAN MENGGUNAKAN METODE PIECES DI PUSKESMAS PEMANCUNGAN PADANG TAHUN 2018 - Hendra Nusa Putra (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
: E-Puskesmas is an application for health services developed to provide basic services to the community. In the Pemancungan health center there are several problems in the information system, such as inaccurate information caused by the ineffective e-Puskesmas system. The purpose of this study was to analyze the implementation of the e-Puskesmas system using the PIECES method (Performance, Information, Economic, Control, Efficiency & Service). The study was conducted on July 2 to August 2, 2018, the type of research was qualitative with a phenomenology approach, the informants in this study were 6 people. All informants were examined using guidelines for in-depth interviews and observations. Analysis in data processing is done by using collaizi. The results of the analysis found that the implementation of e-Puskesmas was classified as good, although in the implementation of e-Puskesmas there were still some obstacles to the network such as speedy connections that were not optimal other than the security of e-puskesmas access using shared username and password accounts and patient waiting times the old one because the network has a problem. The use of the e-Puskesmas application has been going well but there are still obstacles that interfere with the work of the officers, need to be reported and followed up periodically and should be evaluated on the e-puskesmas system in the patient data input process so that it can improve effectiveness and efficiency in service.